2023
DOI: 10.18178/ijiet.2023.13.5.1873
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Digital Learning of Historical Comics on Students‘ Critical Thinking Skills

Abstract: Comics provide a visual, inventive, and sequential reading experience for students learning on their own. Both comics and history present narratives in chronological order. Students pay less attention to reading historical literature, requiring them to put more emphasis on their thinking skills. The author intends to determine how historical comic learning affects students’ critical thinking skills. This quasi-experimental mixed-method design included pre- and post-tests and interview group. A total of 184 stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
1
1
0
Order By: Relevance
“…and look for solutions and learn various things they don't know yet. The findings of this study align with the research conducted by Setyowati et al (2023), which suggests that comics are efficacious in enhancing students' critical thinking abilities. (Azmy,et al 2020; Dini, et al 2023;Putri, et al 2018;Rahayu & Kuswanto, 2021;Shabrina & Kuswanto, 2018).…”
Section: Research Proceduressupporting
confidence: 87%
“…and look for solutions and learn various things they don't know yet. The findings of this study align with the research conducted by Setyowati et al (2023), which suggests that comics are efficacious in enhancing students' critical thinking abilities. (Azmy,et al 2020; Dini, et al 2023;Putri, et al 2018;Rahayu & Kuswanto, 2021;Shabrina & Kuswanto, 2018).…”
Section: Research Proceduressupporting
confidence: 87%
“…Another study revealed that digital comic media could enhance learning outcomes, with results in cycle I at 61% and an increase in cycle II to 93% (Narestuti et al, 2021). The effectiveness of comic media in improving students' thinking skills is also supported by previous research by Setyowati et al (2023), which stated that the N-gain test results showed the critical thinking skills of the treatment group at 61.8% (medium) and the control group at 38.2% (low).…”
Section: Effectiveness Of Video-assisted E-comic Media In Usage Trialsmentioning
confidence: 64%